Single-Spine Agricultural Extension System Governance Structures And Adoption Of Agricultural Technological Innovations - Mwambu, Paul; Karyeija, Gerald Kagambirwe; Mwesigye, Edgar Kateshumbwa; Ramadhan, Hizaamu (Archives of Business Research, 2023)
This study analyzed the governance structures of the single spine agricultural extension system and their effects on adoption of technological innovations by farmer groups in Kiryandongo and Rukungiri Districts of Uganda. This was premised on the view that despite introduction of the single spine agricultural extension service as a policy intervention to increase adoption of innovations for agricultural production and productivity in 2016, four years down the road, these aspirations have not been realized. The research adopted a cross sectional case study design underpinned by the constructivism paradigm. A none-mathematical sampling method was used for key informants and focus group discussions. Data from documents review was triangulated with that from interviews and formed the basis for analysis of findings and report writing. The findings indicated that the limited attention given to the governance structures was one of the fundamental factors that negatively impacted on adoption of agricultural innovations. Failure to provide sufficient resources for monitoring policy implementation undermined the very essence for which it was contrived. It is recommended that the same Ministry strengthens partnerships with the private sector and other non-state actors by taking the lead role in delivery of extension services. This is premised on the notion that District Local Governments have the institutional mandate and structures while the private sector and non-state actors wield the needed resources for enhancing the adoption of agricultural innovations.